Ion temperature measurements of L-mode filaments in MAST by retarding field energy analyser. (19th February 2016) - Allan, S Y; Elmore, S; Fishpool, G; Dudson, B
Abstract: Retarding field energy analysers (RFEAs) have been used to compare the ion temperature ( T i ) of large plasma filaments with the background plasma (composed of small scale filaments) at the midplane and divertor target in L mode discharges in the Mega Amp spherical tokamak (MAST). At low densities, at the midplane and divertor, at distances from 2 to 4 cm from the separatrix the temperature of ions in large filaments was found to be 2 to 3 times larger than the background plasma. At the midplane, the electron temperature for both large filaments and background plasma was around 3 to 7 times smaller than the ion temperature and had a flat profile across the scrape off layer (SOL). At higher densities, at the midplane and divertor, both the filament and background ion temperatures were smaller than at low density. At the midplane, the filament and background ion and electron temperature profiles across the SOL were relatively flat and of comparable magnitude, ranging in temperature from 5 to 25 eV.